The Effectiveness of The Settlement of Alleged Criminal Offences of Insult or Defamation Through Electronic Media with Restorative Justice at The Investigation Stage - Heriyanto, Heriyanto; Saputra, Tri Eka; Ichsan, Nursyamsi; Susanto, Cristofer (IJBLE Scientific Publications Community Inc., 2022)
Restorative justice aims for legal settlement to create an agreement on the settlement of criminal cases. This research study aims to find the effectiveness of the settlement of alleged criminal offences of insult or defamation through electronic media at the investigation stage. This type of research is descriptive qualitative research using a combination approach between doctrinal (normative) and non-doctrinal (empirical) research. The results showed that the settlement of alleged criminal offences of insult or defamation through electronic media with restorative justice at the investigation stage has been effective. This is measured by the level of knowledge of Law Enforcement Officials and the public that has been sufficient and the dominant respondent considers that the justice of the victim can be fulfilled through restorative justice. However, there is still a need for regulations at the level of laws that can serve as guidelines for law enforcement officials in handling criminal cases.